Conceptualising Benefits of User-Centred Design for Digital Library Services - Kautonen, Heli; Nieminen, Marko (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
Libraries are increasingly adopting user-centred design (UCD) approaches to the development of their services for the benefit of customers. Less attention is paid to evaluating the activity of designing. To address this managerial question, we present a study that examines UCD performance in the context of digital library services’ development. The study builds on the existing knowledge on library and design evaluation and examines the literature from two theoretical perspectives: performance management and temporalities. As the main contribution of this paper, we introduce the conceptual 360-Degree Temporal Benefits Model, which captures the situation where many stakeholders are involved in a design activity of a digital library service. Application of the model on two cases demonstrates that the stakeholders can assess the benefits of UCD very differently. We argue that the new model helps in framing the change from the measurable design benefits towards more ambitious and ambiguous public values.